PRAKTIK JUAL BELI PULSA LISTRIK PRABAYAR MENURUT KETENTUAN MAZHAB SYAFI’I - Dahlan Dahlan (STIS Nahdlatul Ulama Aceh, 2020)
Buying and selling is part of ta'awun. For buyers, helping sellers who need money (profit), while for sellers also means helping buyers who are in need of goods. Therefore, buying and selling is a noble deed and the perpetrator gets the pleasure of Allah Swt. The prepaid electricity sale and purchase agreement remains valid and does not violate the provisions' as long as the seller and the buyer share the good faith not to cheat (free from attempts of fraud or tadlis or trickery or taghir). Both the seller and the buyer are aqil baligh, adult and legally competent. Sale and purchase is an agreement to exchange objects (goods) that have value, on the basis of a willingness (agreement) between two parties in accordance with the agreement or provisions justified by the syara.